Toksisitas Daun Mengkudu (Morinda citrifolia L.) sebagai Mat Elektrik terhadap Kematian Nyamuk Aedes aegypti - Dwi Annarya Ning Tyas; Ngadino Ngadino; Iva Rustanti Eri W (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2022)
Dengue Hemorrhagic Fever (DHF) in Indonesia has increased from year to year. Community usually used chemical insecticides to control dengue fever. However, the continuous use of chemical insecticides will have a negative impact on the environment and humans and the possibility of resistance to mosquitoes. An alternative that can be done is to use a bioinsecticide made from noni leaves (Morinda Citrifolia L.) which contains flavonoids, saponins and alkaloids. This study aimed to analyze the toxicity of noni leaf (Morinda citrifolia L.) as an electric mat to the death of the Ae. aegypti. The type of research is a quasi-experimental study with a posttest only research design with a control group design using 4 variations of 1 gram, 1.5 gram, 2 gram, 2.5 gram with five repetitions. The samples used were 25 Ae. aegypti mosquitoes. Statistical analysis used is One Way Anova Test and Probit Test. The results of the average percentage of deaths during 24 hours of observation were 30%, 41%, 54% and 68%. One Way Anova test showed the value (p-valuee=0.000). The probit test showed the LC50 of 1.735 gram/6m3. The conclusion of this research is noni leaf has toxicity to kill the Ae. aegypti mosquito. However, its effectiveness is still below the WHO requirements because it has not reached 90%.